2010
DOI: 10.1002/jcla.20372
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic impact on serum levels of complement component 3 in Japanese patients

Abstract: The aim of this study was to explore the association between the serum concentration of complement component 3 (C3) and a variety of metabolic parameters. The study involved 125 patients in our outpatient clinic. Anthropometric and clinical laboratory data were collected and statistical associations between the serum concentration of C3 and other parameters were evaluated in a cross-sectional as well as a prospective manner. A group of male patients with metabolic syndrome (Mets, n=35) were characterized by ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…A complement cascade is activated within the sites of connective tissues and atherosclerotic lesions . The authors have previously demonstrated that male patients with metabolic syndrome showed higher concentrations of serum C3, and C3 is closely related to insulin resistance . In IgAN patients, we also have indicated that the serum C3 level is closely related to nutritional status, metabolic syndrome, and the prognosis of the patients .…”
Section: Discussionmentioning
confidence: 90%
“…A complement cascade is activated within the sites of connective tissues and atherosclerotic lesions . The authors have previously demonstrated that male patients with metabolic syndrome showed higher concentrations of serum C3, and C3 is closely related to insulin resistance . In IgAN patients, we also have indicated that the serum C3 level is closely related to nutritional status, metabolic syndrome, and the prognosis of the patients .…”
Section: Discussionmentioning
confidence: 90%
“…16,17 The complement system has been hypothesized to play a role in the development of MetS and may be involved in deranged postprandial lipid metabolism in this setting. [18][19][20] C3 may play a particularly strong role in HIV-associated cardiometabolic disease. In this study, C3 was higher in HIV + patients with MetS but was not correlated with other inflammatory biomarkers, potentially indicating a unique role for C3 in this population.…”
Section: Discussionmentioning
confidence: 99%
“…Recent previous studies showed that increased complement levels were related to extreme adiposity and insulin resistance [33], [34]. On the contrary, a few studies suggested complement activation in patients with very low BMI such as anorexia nervosa [35][37].…”
Section: Discussionmentioning
confidence: 99%